DEFENDING THE STATE THROUGH LOCAL FOOD CAMPAIGN ON INTERNET MEDIA - Handayani, Lusia; Nahrawi, Munawar K. (Jurnal Pertahanan dan Bela Negara, 2018)
Food is the fundamental right of every human being. Communities or nations that are not satisfied with food sufficiency will have the potential to cause economic instability and even to bring down a government. Dependence on rice as a staple food can threaten economic and political stability when food is not adequately covered. One alternative that can be made to avoid the threat is to switch to other carbohydrates-based foods that grow in Indonesia, including sweet potato, cassava, arrowroot, and ganyong. However, those local food variety is still considered as second-class food, due to the persistence to rice-eating culture. Therefore, there is a necessity to create a local food campaign on internet media. The Internet is now growing into a medium capable to reach all kinds of people in a quick and precise manner. This descriptive study uses secondary data such as books and journals related to state defense and food security. The study finds that the use of internet as a medium for local food campaign to the community has not been implemented optimally, both by the government and non-government. In line with the rapid development of the internet and the importance of defending the country in all aspects, local food campaigns through internet media require the participation of all stakeholders. Â Keywords: defending of the state, local food campaign, internet